Child Find Activities Between Public School Personnel: Engagement, Barriers, and Experiences - Lane, Julie M.; Jones, David R. (Journal of the American Academy of Special Education Professionals, 2022)
Under the Individuals with Disabilities Education Act, local education agencies or school districts are responsible to conduct child find activities within their agency or district boundaries. This responsibility entails collaborating with private school personnel on an annual basis. Through this qualitative study with a grounded theory approach, we explored the nature of interactions between public and private school personnel as they pertained to child find activities. This inquiry represents the first exploration of relationships between private and public schools within the context of child find activities.